2012
DOI: 10.1111/j.1439-0264.2011.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymelous Layer Chick Displaying Additional Malformations of the Hind Gut: Case Report and In‐Depth Review of Related Literature

Abstract: A case report of a male 6-day-old male layer chick featuring incomplete polymelia of the hind limbs and hindgut malformations is presented. The chick was submitted to computed tomography (CT) examination and subsequent anatomical dissection. Apart from the two supernumerary hind limbs, the anatomical dissection revealed additional hindgut alterations: three uniform-sized caeca flanked the ileum, and the rectum branched into paired cloacae. The supernumerary hind limbs were localized caudal to the normal hind l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…Although clinical and radiographic examinations revealed no other obvious malformations in the present case, an MRI or CT scan was essential to document the complete absence of any other defects. In this respect, CT findings of a previous case of polymelia revealed additional hindgut alterations including three uniform-sized ceca flanking the ileum and a rectum that branched into paired cloacae (6).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although clinical and radiographic examinations revealed no other obvious malformations in the present case, an MRI or CT scan was essential to document the complete absence of any other defects. In this respect, CT findings of a previous case of polymelia revealed additional hindgut alterations including three uniform-sized ceca flanking the ileum and a rectum that branched into paired cloacae (6).…”
Section: Discussionmentioning
confidence: 96%
“…According to the available literature, two case reports recorded this defect in a 6-day-old male layer chick featuring incomplete polymelia of the hind limbs and hindgut malformations (6) and in a 7-wk-old slaughterhouse chicken (2). This report records-for the first time-the surgical treatment and outcome of polymelia in a 7-mo-old layer chicken.…”
mentioning
confidence: 99%
“…the causes for the occurrence of these embryological disorders could be genetic, environmental (infectious agents, toxic plants, chemical substances, physical damage and nutritional deficiencies) or multifactorial (FELIPE, 2003;McGEADY et al, 2006;raDOStItS et al, 2007;hIrSChBerG et al, 2012), varying according to the type of agent and gestational period, and may occur in any anatomical region (ahMaDY and LISEY, 2009). However, malformations can occur in a sporadic way with no specific cause (FeLIPe, 2003;McGeaDY et al, 2006;raDOStItS et al, 2007) which could be the case with the animal in this study, since there were no accidents reported with the progenitors and no medications were administered during gestation.…”
Section: Discussionmentioning
confidence: 99%
“…they may be related to the erratic spread of germ cells in the embryo, or to the abnormal duplication of those cells at the beginning of the embryo development (CeBrIÁN et al, 2006;ahMaDY and LISeY, 2009;McGeaDY et al, 2006). extra limbs have no function (FeLIPe, 2003;hIrSChBerG et al, 2012). However, walking difficulties can cause distress to the animal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation